Multi-scale mechanical characterization of prostate cancer cell lines: Relevant biological markers to evaluate the cell metastatic potential - Zouaoui, J.; Trunfio-Sfarghiu, A.M.; Brizuela, L.; Piednoir, A.; Maniti, O.; Munteanu, B.; Mebarek, S.; Girard-Egrot, A.; Landoulsi, A.; Granjon, T. (Biochimica et biophysica acta. General subjects, 2017)
Considering the importance of cellular mechanics in the birth and evolution of cancer towards increasingly aggressive stages, we compared nano-mechanical properties of non-tumoral (WPMY-1) and highly aggressive metastatic (PC-3) prostate cell lines both on cell aggregates, single cells, and membrane lipids. Cell aggregate rheological properties were analyzed during dynamic compression stress performed on a homemade rheometer. Single cell visco-elasticity measurements were performed by Atomic Force Microscopy using a cantilever with round tip on surface-attached cells. At a molecular level, the lateral diffusion coefficient of total extracted lipids deposited as a Langmuir monolayer on an air-water interface was measured by the FRAP technique. At cellular pellet scale, and at single cell scale, PC-3 cells were less stiff, less viscous, and thus more prone to deformation than the WPMY-1 control. Interestingly, stress-relaxation curves indicated a two-step response, which we attributed to a differential response coming from two cell elements, successively stressed. Both responses are faster for PC-3 cells. At a molecular scale, the dynamics of the PC-3 lipid extracts are also faster than that of WPMY-1 lipid extracts. As the evolution of cancer towards increasingly aggressive stages is accompanied by alterations both in membrane composition and in cytoskeleton dynamical properties, we attribute differences in viscoelasticity between PC-3 and WPMY-1 cells to modifications of both elements. A decrease in stiffness and a less viscous behavior may be one of the diverse mechanisms that cancer cells adopt to cope with the various physiological conditions that they encounter. [Display omitted] •PC-3 cellular pellets are more deformable than WPMY-1 during dynamic compression.•Single cells PC-3 are also more deformable upon indentation-induced stress.•Relaxation after indentation was a two-step process for both cell lines.•Both steps are faster for PC-3 cells than for WPMY-1.•A differential response from two cell elements successively stressed may be argued.•At molecular scale, dynamics of PC-3 lipid extracts are faster than that of WPMY-1.